Arginase occurrence, development and distribution in various organs of rainbow trout (Oncorhynchus mykiss) - Ozan, ST; Erisir, M; Saglam, N (Scientific Technical Research Council Turkey, 1999)
Arginase (L-arginine amidinohydrolase; E.C. 3.5.3.1) enzyme activity levels in sperm, egg, fertilized egg and larvae (up to 25 weeks) of rainbow trout (Oncorhynchus mykiss) taken from Firat University, Faculty of Fisheries, Cip Fish Breeding Station were observed weekly. When the organs of rainbow trout were dissected under microscope, enzyme distribution in organs were investigated. Arginase activities in sperm, egg, fertilized egg and rainbow trout (up to 3 weeks) were at unmeasurable level. Increase of enzyme activity was observed in fish after third week. Between the three and twenty five weeks of larvae arginase activity levels were between 0.018 +/- 0.001 and 4.31 +/- 0.26 units. The organs were dissected when the fish became 8 month old. The distribution of arginase activity in tissues dissected between 8 and 18 months was examined; In kidneys 3.76 +/- 3.07, skin 2.52 +/- 1.88, eyes 0.63 +/- 0.30, liver 19.08 +/- 4.05, muscle 1.01 +/- 0.73 and in the gill 1.33 +/- 0.50 units. Arginase activity of digestive system and spleen were at unmeasurable level.
Alabalik (Oncorhynchus mykiss) Arginazinin Oluşumu, Gelişimi ve Çeşitli Organlardaki Da?ilimi
Keywords: rainbow trout (Oncorhynchus mykiss); arginase